2019
DOI: 10.1038/s41598-019-39487-6
|View full text |Cite
|
Sign up to set email alerts
|

A novel benzamine lead compound of histone deacetylase inhibitor ZINC24469384 can suppresses HepG2 cells proliferation by upregulating NR1H4

Abstract: Histone deacetylases (HDACs) can enzymatically transferred acetyl functional group from protein or lysine residues of histone, so they can regulate the expression of lots of genes. Now HDACs are used as drug targets and many HDAC inhibitors (HDACis) were approved for cancer therapy or in clinical trials. However, the physiological mechanisms and regulatory processes of HDACi anti-cancer effects are largely unexplored and uncompleted. Here we use the virtual screening workflow obtained 25 hit compounds and ZINC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Histone deacetylase inhibitors (HDACis) are potent epigenetic modulators that have various therapeutic potential and have pleiotropic effects at the cellular and systemic levels [25]. While HDACis in anti-cancer therapy are commonly known as apoptosis inducers through anti-cancer gene expression and cell cycle arrest, recent studies have shown anti-tumor efficacy of HDACis in certain cancer types [26][27][28][29]. CG-745 is a HDAC inhibitor, and it has been reported as a potent anti-cancer agent in cholangiocarcinoma, pancreatic cancer, prostate cancer, and non-small cell lung cancer [30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Histone deacetylase inhibitors (HDACis) are potent epigenetic modulators that have various therapeutic potential and have pleiotropic effects at the cellular and systemic levels [25]. While HDACis in anti-cancer therapy are commonly known as apoptosis inducers through anti-cancer gene expression and cell cycle arrest, recent studies have shown anti-tumor efficacy of HDACis in certain cancer types [26][27][28][29]. CG-745 is a HDAC inhibitor, and it has been reported as a potent anti-cancer agent in cholangiocarcinoma, pancreatic cancer, prostate cancer, and non-small cell lung cancer [30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…An analysis based on the TCGA dataset indicated that NR1H4 was downregulated in liver cancer. This suggests that NR1H4 may play an important role in tumorigenesis [39]. If bile acid levels increase, FXR activates the expression of SHP and then SHP inhibits transcription of NTCP [40].…”
Section: Discussionmentioning
confidence: 99%
“…This new class of HDAC inhibitors possesses an imidazopyridine moiety, which, to the best of our knowledge, has not been reported before. The inhibition of various HDACs by these compounds as well as their effects on acetylated histones, pro-apoptotic and antiapoptotic markers, cell cycle and anti-proliferative activity in the MCF7 breast cancer cell line were investigated [14][15][16] and are reported herein.…”
Section: Introductionmentioning
confidence: 99%